2007
DOI: 10.1038/sj.cgt.7701104
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-10 gene transfer to peritoneal mesothelial cells suppresses peritoneal dissemination of gastric cancer cells due to a persistently high concentration in the peritoneal cavity

Abstract: Interleukin (IL)-10 has potent biological properties including an inhibitory action on the proliferation and metastasis of various cancer cells. However, it is difficult to maintain a high concentration of this cytokine as it has a short half life. In this study, we evaluated whether peritoneal mesothelial cells (PMCs) could be suitable for maintaining a high concentration of IL-10 using adenoviral gene transfer. We also evaluated the therapeutic effects of an intraperitoneal injection with adenoviral vector c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 32 publications
0
11
0
1
Order By: Relevance
“…We show here, utilising an in vitro simulation to generate M1 and M2 macrophage phenotypes, that there is a phenotype dependent response to IL-10 in terms of VEGF production. This data is important as it supports the increasing challenges to the traditional paradigm for the role of M1 (NOS2 + cells) and M2 (arginase-1 + cells) phenotypes in pathological angiogenesis and moreover, the potential utilisation of IL-10 as an anti-angiogenic therapy (Silvestre et al, 2000;Tanaka et al, 2008). This current data shows that IL-10 is able to inhibit M1-stimulated VEGF (LPS/CGS21680-conditioned NOS2 + macrophages) and not M2-stimulated VEGF production (PGE2-conditioned arginase-1 + macrophages).…”
Section: Discussionmentioning
confidence: 74%
“…We show here, utilising an in vitro simulation to generate M1 and M2 macrophage phenotypes, that there is a phenotype dependent response to IL-10 in terms of VEGF production. This data is important as it supports the increasing challenges to the traditional paradigm for the role of M1 (NOS2 + cells) and M2 (arginase-1 + cells) phenotypes in pathological angiogenesis and moreover, the potential utilisation of IL-10 as an anti-angiogenic therapy (Silvestre et al, 2000;Tanaka et al, 2008). This current data shows that IL-10 is able to inhibit M1-stimulated VEGF (LPS/CGS21680-conditioned NOS2 + macrophages) and not M2-stimulated VEGF production (PGE2-conditioned arginase-1 + macrophages).…”
Section: Discussionmentioning
confidence: 74%
“…Unfortunately, the half-life of IL10 is only approximately 20 minutes and it is difficult to maintain a high concentration after administration of recombinant protein (27). Nonreplicating adenovirus-mediated delivery has shown promise in retaining therapeutically effective levels of IL10 in vivo (28). Given its pleiotropic effects, IL10 may be an effective agent with which to improve the antitumor potential of vaccinia virus.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, Tanaka et al demonstrated that intraperitoneal IL-10 gene transfer to the peritoneal mesothelium using an adenoviral vector suppressed peritoneal dissemination of MKN45 gastric cancer cells [126]. However, IL-10 is an -17-immunosuppressive cytokine [127,128].…”
Section: Immunotherapymentioning
confidence: 99%